The role of lawfulness and legality toward purchasing counterfeits of luxury brands - Dix, Steve; Phau, Ian (University of Western Sydney, 2008)
This study examines the influence of personality factors and attitudes toward consumers' willingness to knowingly purchase counterfeit luxury brands. The findings have uncovered contrasting evidence that attitudes do not influence consumers' willingness to purchase counterfeit luxury brands. Integrity has been noted to be a strong influencer of both attitudes and consumer willingness to purchase consistently. Both buyers and non-buyers were tested for their attitudinal differences. Status consumption and materialism did not play a role in influencing attitudes or willingness to purchase. Further managerial implications were provided to better allow luxury brand owners, the government and policy makers to better understand consumers of counterfeit luxury brands.